Mitochondrial Myopathy and Hypotonia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Three children with hypotonia, cardiac impairment, and defects of the mitochondrial respiratory chain complexes, but no ragged red fibers, are reported from the Hopital de la Timone, Chemin de l'Armee, d'Afrique, Marseille, France.